2004
DOI: 10.1103/physrevb.70.064519
|View full text |Cite
|
Sign up to set email alerts
|

Successive superconducting transitions and Anderson localization effect inTa2S2C

Abstract: A complex carbide Ta2S2C consists of van der Waals (vdw)-bonded layers with a stacking sequence · · · C-Ta-S-vdw-S-Ta-C-· · · along the c axis. The magnetic properties of this compound have been studied from DC and AC magnetic susceptibility. Ta2S2C undergoes successive superconducting transitions of a hierachical nature at T cl = 3.61 ± 0.01 K [H (l) c1 (0) = 28 ± 2 Oe and H (l) c2 (0) = 7.7 ± 0.2 kOe] and Tcu = 9.0 ± 0.2 K [H (u) c2 (0) = 6.0 ± 0.3 kOe]. The intermediate phase between Tcu and T cl , where δχ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2005
2005
2007
2007

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(15 citation statements)
references
References 34 publications
2
13
0
Order By: Relevance
“…III D and is compared with that of T cu (H) and T cl (H). 1 In Sec. IV A we will show that ρ at H = 50 kOe is proportional to ln T at low temperatures.…”
Section: Results a Electrical Resistivitymentioning
confidence: 99%
See 4 more Smart Citations
“…III D and is compared with that of T cu (H) and T cl (H). 1 In Sec. IV A we will show that ρ at H = 50 kOe is proportional to ln T at low temperatures.…”
Section: Results a Electrical Resistivitymentioning
confidence: 99%
“…In our previous paper, 1 we have shown that the difference δχ (= χ F C − χ ZF C ) shows a kink at T cl = 3.60 K. However, it does not reduce to zero at T = T cl , but exhibit a broad tail above T cl . In Fig.…”
Section: B Onset Of Irreversibilitymentioning
confidence: 99%
See 3 more Smart Citations